Rectal adenocarcinoma with oncocytic features: possible relationship with preoperative chemoradiotherapy. - Rouzbahman, M; Serra, S; Chetty, R (2006)
BACKGROUND: The introduction of preoperative chemoradiation into the treatment protocol of rectal adenocarcinomas has affected the microscopical morphology in subsequent resection specimens. The constellation of histopathological changes is varied and well documented. AIM: To describe oncocytic change in rectal cancers that have been treated with chemoradiation before surgery. METHODS: 7 of 54 patients with rectal cancer were identified with a history of chemoradiation, specifically directed to the rectal tumours in fractions of 4500-5000 cGy of radiation and 5-fluorouracil. The rectal tumours in five of these seven patients were composed of oncocytes that constituted 30-80% of the cancers. The patients were three men and two women aged 65-73 years, all with T3 N0 tumours. The intervals between chemoradiation and resection varied from 3 to 12 weeks. RESULTS: The tumour cells conformed to oncocytes morphologically (large size with abundant, granular eosinophilic cytoplasm, vesicular nuclei and prominent acidophilic nucleoli), immunohistochemically (positive for carcinoembryonic antigen, cytokeratin 20 and caudal type homeo box transcription factor 2, but negative for both chromogranin and synaptophysin) and ultrastructurally (large cells showing tight junctions, cytoplasmic engorgement by mitochondria and absence of neurosecretory granules). CONCLUSIONS: The changes in these cells differ from those described previously in endocrine cells encountered in pretreated rectal cancers. Oncocytic change in this particular clinical context occurs as a reflection of cytotoxic damage or cellular hypoxia induced by chemoradiation resulting in degeneration of the cell and the oncocytic phenotype. Oncocytic change may be an under-recognised histopathological change in rectal cancers receiving preoperative chemoradiation.